Kontaktallergien bei Senioren - Mahler, Vera (Hautarzt, 2015)
The percentage of seniors (> 65 years of age) in the general population continues to rise. Their sensitization profile may be influenced by lifelong work-related and nonwork-related exposures and comorbidities requiring local or systemic treatment. Recent analysis of the IVDK (Information Network of Departments of Dermatology) cohort concerning the most frequently recognized contact allergens in the age group above 65 (2009-2013: N = 14,841) revealed significant differences compared to the age group up to 65 years of age. The top 10 contact allergens recognized in individuals older than 65 years were the following: fragrance mix, Myroxylon pereirae (Balsam of Peru), nickel (II) sulfate, fragrance mix II, colophony, propolis, methylchloroisothiazolinone/methylisothiazolinone (MCI/MI), lanolin alcohol, Amerchol L 101, tert-butylhydroquinone. Sensitization to nickel was significantly less frequent, while sensitizations to fragrance mix and Balsam of Peru were significantly more frequent than in the age group up to 65 years of age. The percentage of patients with leg dermatitis was 25.9 % in the age group above 65 (versus 5.8 % in the age group up to 65 years of age). The analysis of the subgroup over 65 years of age with and without ulcer/stasis dermatitis/chronic venous insufficiency displayed remarkable differences in sensitization frequencies against ingredients of topical ointments (lanolin alcohol, Amerchol L 101, and tert-butylhydroquinone). If these comorbidities exist, patch testing of the topical ointment series parallel to the standard series is worthwhile.
EVALuna2:19550